Relationships as determinants of substance use amongst street children in a local government area in south-western Nigeria - Akindele O. Adebiyi; Eme T. Owoaje; Michael C. Asuzu (South African Family Practice)
Background: Unrestrained exposure to street life often makes the street child vulnerable to psychoactive substances. In other settings, the social relationships of the substance user with those around him or her and family norms of parenting have been documented to modulate use. However, there is a dearth of literature on the role of relationships in substance use in Nigeria.